Anti‐inflammatory effect of alkaloids extracted from Dendrobium aphyllum on macrophage RAW 264.7 cells through NO production and reduced IL‐1, IL‐6, TNF‐α and PGE2 expression. (17th November 2019) - Wang, Qin; Liang, Jiaxi; Stephen Brennan, Charles; Ma, Lukai; Li, Yanfu; Lin, Xiaohui; Liu, Huifan; Wu, Jihong
Summary: Dendrobium aphyllum is an edible plant that is used as a functional food to improve health. We previously examined peptides and polysaccharides extracted from Dendrobium aphyllum ; however, we did not investigate D . aphyllum's alkaloid compounds and their functions. In this study, we detail the composition of alkaloids from Dendrobium aphyllum (DAA), including 2α, 3β‐dihydroxy nortropane, 1‐methyl‐2‐[(4Z, 7Z)‐4, 7‐tridecadienyl]‐4(1H)‐quinolone and maokonine, which were first identified by UPLC‐MS analysis. Furthermore, the anti‐inflammatory activity of DAA on LPS‐induced RAW 264.7 macrophages was examined. DAA treatment inhibited LPS‐induced NO production and decreased ( P  < 0.05) IL‐1, IL‐6, TNF‐α and PGE2 secretion in the RAW 264.7 macrophages. DAA treatment also inhibited COX‐2 and iNOS mRNA expression in a dose‐dependent manner, indicating that these compounds can attenuate the synthesis of the above‐mentioned molecules at the transcriptional level, tentatively confirming their anti‐inflammatory effect. Abstract : Table of content.